2017
DOI: 10.18203/2320-1770.ijrcog20174041
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in pregnancy with heart disease in tertiary care hospital in India

Abstract: Background: Cardiac disease is an important cause of maternal mortality and morbidity both in antepartum and postpartum period. The overall incidence of heart disease in pregnancy is <1%. Objective of present study was to determine maternal outcome in pregnant women with heart diseases in terms of fetal complication, maternal complication and Mode of delivery.Methods: This study was conducted in the Department of Obstetrics and Gynaecology at Government Lalla Ded Hospital, an associated of Government Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
4
9
1
Order By: Relevance
“…We found that, despite mothers suffering from heart disease, most of their pregnancies are full-term (the term “pregnancy” was defined as a live birth from 37 completed weeks to less than 42 completed weeks of gestation [17]). Furthermore, in this study, overall, RHD was much more common than CHD, which was consistent with previous studies [18,19,20,21]. The explanation for this can be due to the lack of preventive treatment and inadequate use of secondary antibiotic prophylaxis against streptococcal infections in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that, despite mothers suffering from heart disease, most of their pregnancies are full-term (the term “pregnancy” was defined as a live birth from 37 completed weeks to less than 42 completed weeks of gestation [17]). Furthermore, in this study, overall, RHD was much more common than CHD, which was consistent with previous studies [18,19,20,21]. The explanation for this can be due to the lack of preventive treatment and inadequate use of secondary antibiotic prophylaxis against streptococcal infections in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
“…We found that mitral valve regurgitation was predominantly due to valvular lesions (40.12%). However, most previous studies indicated that mitral valve stenosis was more common [15,18,19,20,21,22]. The reason might be that our study only concentrated on pregnant mothers after 22 weeks of gestation, whereas others included mothers over the whole pregnancy period.…”
Section: Discussionmentioning
confidence: 96%
“…Mortality in pregnant females with cardiac diseases is mainly due to cardiac failure and pulmonary oedema. In our study out of 100 patients 2 were died due to cardiac failure and sepsis which was comparable to the study done by Saima Salam 12 and Kamat. 13 Both were of term gestation and one was delivered vaginally developed peripartum cardiomyopathy and the other a known case of congenital heart disease delivered through caesarean section.…”
Section: Discussionsupporting
confidence: 88%
“…Peripartum cardiomyopathy (40.9%) was the leading cause of cardiac morbidity in our study, and it was the only cause of cardiac-related maternal mortality. That was unlike in most parts of India, where rheumatic heart disease and congenital heart diseases were the leading cause of morbidity and mortality [ 27 - 28 ]. It may be because most of the valvular heart diseases were diagnosed early in the pregnancy and hence optimized adequately before delivery, whereas cardiomyopathies are usually diagnosed late.…”
Section: Discussionmentioning
confidence: 99%